Role of Mitochondria in the Production of RNA-Containing Tumor Viruses - Bader, Artrice V. (1973)
The role of mitochondria in the reproduction of RNA-containing tumor viruses was examined by using ethidium bromide (EB) to induce degenerative effects in mitochondria. The effects of EB in murine and avian cells were monitored by electron microscopy. Chronically infected mouse (JLS-V5) cells, in which extensive mitochondrial changes were induced, continued to produce murine leukemia virus. Also, complete reproductive cycles of Rous sarcoma virus (RSV) occurred in newly infected chicken embryo cells exposed to EB. Morphological transformation characteristic of infection of chicken embryo cells by RSV occurred in cells which contained induced aberrant mitochondria. The results demonstrate that mitochondria play a relatively minor role, if any, in the reproduction of RNA-containing tumor viruses.